Assessment of the Implementation of the Islamic Studies Curriculum in Senior High Schools - Owoyale-Abdulganiy; Ibrahim Solahudeen; Abdulwaahid Tiamiy (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
In recent times, many students have cheated on exams. Factors related to curriculum content activities and successful completion of all topics expected to be taught to students at various levels of Islamic education, within the specified time period were found to be very ineffective in today's schools. This research aims to examine the implementation of the Islamic studies curriculum in senior high schools. A descriptive survey design was used in this study. A total of 9,231 people constituted the study population while three hundred and sixty eight (368) participants were sampled using Krejcie and Morgan's sampling table. Five (5) research questions were asked and answered. The collected data was analyzed using descriptive statistics with the help of the Statistical Package for Social Sciences. The research design adopted for this study is a descriptive survey.  The research results show that the availability of qualified Islamic studies teachers is necessary for the successful implementation of the Islamic Studies curriculum in high schools. Considering these findings, the research concludes that the use of appropriate teaching methods in teaching the Islamic Studies curriculum has proven to be effective because qualified teachers and teacher capacity development increase the success of implementing the Islamic Studies curriculum which has not yet been fully implemented in senior secondary schools. Implications of this research can provide insight into the effectiveness of curriculum implementation, identify challenges faced in the learning process, and offer recommendations for improvements to improve the quality of Islamic Studies education.